Laser-induced breakdown spectroscopy and its applications in mineral and pollution analyses - Haider, A F M Yusuf; Abedin, K.M. (© 2012 Nova Science Publishers, 2017)
This book chapter was published in the book Advances in Laser and Optics Research. Volume 9 [© 2012 Nova Science Publishers, Inc.] and the definite version is available at: https://www.novapublishers.com/catalog/product_info.php?products_id=20462